Role of energy storage in energy and water security in Central Asia. (June 2022) - Zakeri, Behnam; Hunt, Julian David; Laldjebaev, Murodbek; Krey, Volker; Vinca, Adriano; Parkinson, Simon; Riahi, Keywan
Abstract: Central Asia has faced major energy and water security challenges. Technically, water from the Pamir and Tian Shan Mountain ranges could be sufficient to meet the needs of the countries in the region, if there was no temporal mismatch between the availability of water for irrigation and electricity generation. While water is required for agriculture in downstream countries during the summer, demand for hydro electricity generation is mainly in the wintertime in upstream countries. With the aid of the open-source MESSAGEix energy systems optimization modelling framework, we study a renewable energy transition in the region through to 2050, considering innovative long duration water and energy storage solutions for optimal management of water and energy resources in different seasons. The modelling approach demonstrates that the proposed "dual water and energy storage scheme", with two different hydrological cycles for up- and down-stream regions, can guarantee enough water for energy generation in upstream countries in winter while ensuring water availability for irrigation downstream in summer. This scheme is economically feasible and, with further detailed analyses and geo-political considerations, it can serve to improve energy security and water resource management, towards achieving sustainable development goals in Central Asia. Highlights: A solution for transboundary water and energy conflict in Central Asia is proposed. Benefits of energy storage beyond the energy sector are shown. Long duration energy storage is key for high shares of solar PV and wind energy in the region. An open-access, integrated water and energy system model of Central Asia is developed. Central Asia's energy transition to a high share of renewable energy by 2050 is analyzed.